2008
DOI: 10.1002/aqc.1004
|View full text |Cite
|
Sign up to set email alerts
|

Detritus accumulation and decomposition in a coastal lake (Acquatina–southern Italy)

Abstract: 1. Knowledge about processes and dynamics underlying organic matter accumulation in transitional waters is crucial for the protection of these ecologically important coastal habitats. This study investigated the relationship between large particle accumulation and decomposition in a coastal lake included in a Site of Community Interest (SCI) using sediment trap and litterbag techniques. 2. Two sets of sediment traps were deployed at five sites along the longitudinal axis of the lake. One set was emptied once a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Pace et al (2004) and Costantini et al (2008) found a strong dependency of detritus accumulation on allochthonous primary producers in both brackish and freshwater ecosystems. Osleger et al (2008) observed that land use around Clear Lake strongly influenced the chemistry of sediments and cyanobacterial population structure.…”
Section: Discussionmentioning
confidence: 99%
“…Pace et al (2004) and Costantini et al (2008) found a strong dependency of detritus accumulation on allochthonous primary producers in both brackish and freshwater ecosystems. Osleger et al (2008) observed that land use around Clear Lake strongly influenced the chemistry of sediments and cyanobacterial population structure.…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately, these differences arise from the different chemical composition of autotrophs, which influences consumption by heterotrophs (Cebrian and Lartigue, 2004;Chase, 2000;Costantini et al, 2008;Nowlin et al, 2008;Shurin et al, 2006). The source, quantity and quality of detritus affect the population density, feeding rates and trophic niche of detritivores and thus their interactions with other species in the web.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, relocating field-collected sediments to new settings, such as the laboratory, may fail to replicate in situ conditions (Orihel and Rooney, 2012). Second, our approach offers a more realistic simulation of long-term mineralisation and decomposition processes than, for example, leaf litterbags, which have been widely used to study biogeochemistry and ecosystem metabolism (Herbst, 1980;Jackson et al, 1995;Longhi et al, 2008;Costantini et al, 2009 The only studies performed at a whole-ecosystem level have focused on removing entire sediment horizons, such as for lake restoration or fisheries management, without manipulating OM directly (Peterson, 1982). New approaches are therefore needed to manipulate natural sediments over large spatial scales.…”
Section: Introductionmentioning
confidence: 99%
“…Ecological studies have rarely manipulated sediments that have been standardised to mimic natural conditions, despite this strategy being fundamental to fields such as environmental toxicology (Suedel and Rodgers, 1994; but see Feuchtmayr et al, 2009). Traditionally, studies have added OM either to fieldcollected sediments, which have been relocated to laboratories or outdoor mesocosms (Wood and Richardson, 2009;Liboriussen et al, 2011;Song et al, 2013), or in situ by burying decomposing leaves into sediment surfaces (Herbst, 1980;Jackson et al, 1995;Longhi et al, 2008;Costantini et al, 2009;Marmonier et al, 2010).…”
Section: Introductionmentioning
confidence: 99%